2021
DOI: 10.3389/fmed.2021.655113
|View full text |Cite
|
Sign up to set email alerts
|

The Seeds of Doubt: Finding Seeds in Intriguing Places

Abstract: Introduction: Seeds may be found in gastrointestinal tissue samples, and their multifaceted appearance may be challenging. The aim is to report a rough incidence of pathology samples which show seeds, specify the most frequent sample types and show an iconography of the most commonly identified seeds.Materials and Methods: Between 2017 and 2020, all gastrointestinal pathology cases in which seeds/seed parts were found, were collected and seed type described by referencing a seed image library.Results: Fifty ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Many different types of seeds can be found in all gastrointestinal samples, as they often remain undigested due to the particular resistance of the seed's external cuticle to digestion. Various types of seeds have been reported in biopsy samples, polypectomy specimens and in various types of surgical specimens including appendicectomies, diverticular disease associated resections and cancers [59,60]. Among the most frequently found seeds, tomato seeds deserve more careful attention due to their complex morphology with glycoprotein-rich villi on the surface (which facilitate adhesion to the intestinal mucosa) making a misdiagnosis as parasites possible (Fig.…”
Section: Seedsmentioning
confidence: 99%
“…Many different types of seeds can be found in all gastrointestinal samples, as they often remain undigested due to the particular resistance of the seed's external cuticle to digestion. Various types of seeds have been reported in biopsy samples, polypectomy specimens and in various types of surgical specimens including appendicectomies, diverticular disease associated resections and cancers [59,60]. Among the most frequently found seeds, tomato seeds deserve more careful attention due to their complex morphology with glycoprotein-rich villi on the surface (which facilitate adhesion to the intestinal mucosa) making a misdiagnosis as parasites possible (Fig.…”
Section: Seedsmentioning
confidence: 99%
“…digested plant structures were categorized as the cases containing food residues. The types of the seeds observed in these cases were identified by comparing them with reference images of seeds and plants in the catalogues (5)(6)(7).…”
Section: Seeds or Parasites? Clinical And Histopathological Features ...mentioning
confidence: 99%
“…The relevant studies are compiled in Table I . Also, we reviewed the literature to identify studies about seed observed in appendectomy specimens without any date or language restriction and compiled the relevant studies in Table II (6,7,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62).…”
Section: Seeds or Parasites? Clinical And Histopathological Features ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the brilliant staining of the eggs of E. vermicularis, raises the possibility that RGB trichrome staining could be a useful tool for the identification of eggs from different nematode and/or other helminth species, and deserves comparative studies for this purpose. While studying the appendix samples to assess E. vermicularis staining, we noticed the presence of occasional undigested seeds and plant residuals that can be eventually confused with parasites and, in fact, several studies have addressed this issue [30][31][32][33] . In this context, we decided to investigate the staining outcomes of seeds and plant tissue remnants after application of RGB trichrome as a method that contributes to its differentiation from parasites.…”
Section: Enterobius Vermicularismentioning
confidence: 99%